2016
DOI: 10.1590/0001-3765201520150344
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological perspectives from Brazilian Salvia officinalis (Lamiaceae): antioxidant, and antitumor in mammalian cells

Abstract: Salvia offi cinalis (Lamiaceae) has been used in south of Brazil as a diary homemade, in food condiment and tea-beverage used for the treatment of several disorders. The objective of this study was to characterize chemical compounds in the hydroalcoholic (ExtHS) and aqueous (ExtAS) extract from Salvia offi cinalis (L.) by gas chromatography-mass spectrometry (GC-MS) and by high-resolution electrospray ionization mass spectrometry (ESI-QTOF MS/MS), evaluate in vitro ability to scavenge the free radical 2,2-diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 30 publications
1
52
0
1
Order By: Relevance
“…The findings of this study are consistent with the literature. It has been found that Brazilian S. officinalis has a DPPH scavenging activity comparable to gallic acid [57]. In addition S. palaestina essential oil showed an increasing DPPH radical scavenging activity in a concentration dependent manner (from 0.122 to 1.35 mg/mL), which was a higher weight concentration than the ones used in this study [58].…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The findings of this study are consistent with the literature. It has been found that Brazilian S. officinalis has a DPPH scavenging activity comparable to gallic acid [57]. In addition S. palaestina essential oil showed an increasing DPPH radical scavenging activity in a concentration dependent manner (from 0.122 to 1.35 mg/mL), which was a higher weight concentration than the ones used in this study [58].…”
Section: Resultsmentioning
confidence: 77%
“…The results showed that ethanol and water extracts of all samples showed moderate radical scavenging activity when compared to standard antioxidants (Figure 2C,F). All of the Salvia species were able to donate electrons to neutralize the DPPH radical, showing a catalase-like, superoxide dismutase (SOD)-like activity [57]. The highest and lowest activities were observed in S. brachyantha and S. aethiopis , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In traditional medicine, it has been used for the treatment of different kinds of disorders including dyspepsia (such as heartburn and bloating), seizure, ulcers, gout, rheumatism, inflammation, dizziness, tremor, diarrhea, hyperglycemia, excessive sweating, atherosclerosis and inflammations in the throat and skin [2][3][4].…”
mentioning
confidence: 99%
“…Caffeic and rosmarinic acids have been frequently reported for S. officinalis extracts (Lu & Foo 1999, 2000, 2001Hossain et al 2010;Roby et al 2013;Martins et al 2015;Garcia et al 2016). They are considered to be potent antioxidant molecules (Khan et al 2016;Nicolai et al 2016;Adomako-Bonsu et al 2017) that also exhibit antimutagenic, anticarcinogenic, antiinflammatory and antiallergenic activities (Konishi et al 2005).…”
Section: Hplc Analysis Presented Inmentioning
confidence: 99%